Data Privacy : a Runbook for Engineers. - Bhajaria, Nishant (Manning Publications Co. LLC, 2022)
Data Privacy: A runbook for engineers teaches you how to navigate the trade-off s between strict data security and real world business needs. In this practical book, you'll learn how to design and implement privacy programs that are easy to scale and automate. There's no bureaucratic process--just workable solutions and smart repurposing of existing security tools to help set and achieve your privacy goals.